Sharia Principles in Improving Justice and Balance in UMKM Cookie Production Patterns - Afifah Salsabila Humairah,; Nadya Safira Anggraini,; Ansa Meilia Safira Maharani,; Masiyah Kholmi, (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2025)
This article aims to examine how the application of sharia principles can improve justice and balance in the production patterns of pastry MSMEs, with a focus on the case study of TM Berkah MSMEs. This research uses a descriptive-qualitative approach through literature study methods and in-depth interviews with business actors who have implemented Islamic values in their production operations. The results show that principles such as al-tawazun (balance), 'is (justice), halal thayyib, and maslahah have been implemented in TM Berkah. This can be seen in the production strategy based on a pre-order system, the use of halal ingredients, a fair wage system, and worker training without discrimination. The application of these principles not only increases production efficiency, but also strengthens the welfare and blessings of the business. The conclusion of this study confirms that the sharia approach can create social and economic stability in the context of micro-enterprises. Recommendations from this study invite other MSMEs to adopt sharia-based production principles and encourage the active role of the government and Islamic financial institutions in providing training, incentives and assistance so that the principles of justice and sustainability can be widely realized in the MSME sector.